Evaluation of the Sustainability of the Sheep Farming Assistance Program Pentahelix Based (POAC Managerial Analysis of the Kayadi Gate Program in Darma District Kuningan Regency, Indonesia) - Bili Nur Muhamad; Hasni Arief; Lilis Nurlina (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
Livestock assistance programs are among the policy instruments widely used in rural poverty alleviation efforts, but their sustainability is often hindered by weak management and poor stakeholder collaboration. This study aims to evaluate the implementation and sustainability of the Gerbang Kaya Program for sheep livestock commodities in Darma District, Kuningan Regency, using the Pentahelix approach and the POAC (Planning, Organizing, Actuating, and Controlling) managerial framework. This study uses a qualitative case study approach. Data were collected through in-depth interviews with key actors involved in the program, including government officials, academics, business leaders, communities, and the media. The results of the study indicate that, in the planning phase, the program has been prepared administratively based on extreme poverty data, but there is still minimal farmer participation, so technical needs and field readiness have not been fully accommodated. In terms of organization, the Pentahelix collaboration is unbalanced; the roles of government and farmers are relatively dominant, while the contributions of academics, business actors, and the media remain limited. This condition affects weak technical support, market access, and information dissemination. In terms of actuation, program implementation showed varying results across recipient groups, influenced by differences in farmers' technical capacity and the intensity of assistance. Meanwhile, the controlling aspect tended to be administrative in nature and was not yet supported by farmer performance or economic indicators. A business sustainability evaluation showed that four out of five farmer groups maintained and developed their sheep farming businesses through population growth and independent reinvestment, while one group experienced total failure due to high livestock mortality. These findings confirm that the sustainability of livestock assistance programs is not solely determined by adherence to POAC managerial principles, but is strongly influenced by the quality of functional, sustainable Pentahelix collaboration. This research contributes to the development of program evaluation studies by emphasizing the importance of analyzing multi-actor collaboration in ensuring the sustainability of community-based livestock empowerment programs.